2017
DOI: 10.1155/2017/3642832
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic CD4+ T Cell Exhaustion Reverses with Clinical Resolution of Pulmonary Sarcoidosis

Abstract: Investigation of the Th1 immune response in sarcoidosis CD4+ T cells has revealed reduced proliferative capacity and cytokine expression upon TCR stimulation. In other disease models, such cellular dysfunction has been associated with a step-wise, progressive loss of T cell function that results from chronic antigenic stimulation. T cell exhaustion is defined by decreased cytokine production upon TCR activation, decreased proliferation, increased expression of inhibitory cell surface receptors, and increased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…CD4 + /PD-1 + T lymphocytes were found to be in close contact with PD-L1 + chronic lymphocytic leukemia cells [ 19 ] and the activated PD-1/PD-L1 axis led to decreased production of IL-4 from CD4 + T lymphocytes [ 19 ]. High level of CD4 + /PD1 + lymphocytes, reduced cytokine secretion, dysfunctional proliferation, and increased apoptosis were also observed among sarcoidosis patents [ 20 , 21 ], but blocking PD-1 pathway in CD4 + T cells could reverse the proliferative capacity [ 21 ]. The expression of PD-1 on CD4 + lymphocytes indicated exhausted function [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4 + /PD-1 + T lymphocytes were found to be in close contact with PD-L1 + chronic lymphocytic leukemia cells [ 19 ] and the activated PD-1/PD-L1 axis led to decreased production of IL-4 from CD4 + T lymphocytes [ 19 ]. High level of CD4 + /PD1 + lymphocytes, reduced cytokine secretion, dysfunctional proliferation, and increased apoptosis were also observed among sarcoidosis patents [ 20 , 21 ], but blocking PD-1 pathway in CD4 + T cells could reverse the proliferative capacity [ 21 ]. The expression of PD-1 on CD4 + lymphocytes indicated exhausted function [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…High level of CD4 + /PD1 + lymphocytes, reduced cytokine secretion, dysfunctional proliferation, and increased apoptosis were also observed among sarcoidosis patents [ 20 , 21 ], but blocking PD-1 pathway in CD4 + T cells could reverse the proliferative capacity [ 21 ]. The expression of PD-1 on CD4 + lymphocytes indicated exhausted function [ 20 , 21 ]. CD4 + /PD1 + TILs were dysfunctional in the presence of PD-L1 among patients with head and neck squamous cell carcinomas [ 22 ] and glioblastoma multiforme (GBM) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary CD4+ T cells from patients with sarcoidosis spontaneously secrete IL-2 ex vivo, but upon TCR stimulation, they express less IL-2 and IFN-γ compared to CD4+ T cells from other lung diseases and healthy controls, in line with an anergic/exhausted phenotype [60]. Other signs of Th1 anergy/exhaustion due to prolonged antigen exposure in sarcoidosis are their reduced proliferative capacity and their higher levels of apoptosis, associated with increased programmed death (PD)-1 expression [61].…”
Section: T Cellsmentioning
confidence: 99%
“…Pulmonary CD4+ T cells from sarcoidosis spontaneously secrete IL-2 ex vivo, but when given TCR stimulation, these cells express less IL-2 and IFN-γ relative to CD4+ T cells from various other lung diseases and healthy control subjects, consistent with an anergic/exhausted phenotype (58). Additionally, sarcoidosis CD4+ T cells have a reduced proliferative capacity and higher levels of apoptosis, along with increased PD-1 expression, which is often associated with persistent antigen exposure to limit chronic T cell activation (59,60). A recent study demonstrated that PD-1 expression was highest on sarcoidosis CD4+ T cells with a Th17 phenotype (61).…”
Section: T Cells In Cbd and Sarcoidosismentioning
confidence: 99%